Kepemilikan Institusional Sebagai Pemoderasi Pengaruh Penjualan Kepada Pihak Berelasi Terhadap Nilai Perusahaan - Ermad M.J; Zulkifli Umar; Supriyanto Supriyanto; Wardayani Wardayani; Elserra Siemin Ciamas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to examine institutional ownership as a moderating effect of related parties sales on firm value. This study is a sample study, which includes a portion of the population into observations selected based on certain criteria. The observation period of research data from 2016-2018 which amounted to 241 samples of manufacturing sector companies listed on the Indonesia Stock Exchange. The analytical method used is moderated regression. The results of this study found that institutional ownership moderates the effect of related parties sales on firm value